Penerapan Perawatan Luka Modern Dressing pada Pasien Ulkus Diabetikum - Irene Maulani Maretha Hutabarat; Sanny Frisca; Vincencius Surani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Diabetic foot ulcer is a disease of the feet of DM sufferers with the characteristics of sensory, motor, autonomic neuropathy as well as macrovascular and microvascular disorders. Diabetic foot injuries are one of the complications that DM sufferers fear because they can result in amputation. Modern Dressing wound treatment with the Moist Wound Healing method is effective in healing ulcer wounds in DM patients. The wound healing method aims to maintain the moisture of the wound by using a moisture-retaining bandage so that wound healing and tissue growth can occur naturally. To determine nursing care in dm patients with leg injuries the application of Modern Dressing wound care using metcovazin and foam in diabetic ulcer patients. This study presents a descriptive study describing the treatment of ulcer wounds in DM patients with Modern Dressing wound treatment using a case study approach. Based on the results of the application of Evidence Based Practice (EBP) dapart, it is concluded that the application of Modern Dressing wound care is more effective than conventional wound treatment. as evidenced by the change in the decreased score in Mrs. N with 3 intervention processes, namely by decreasing the initial score of 30 down to 22 after Modern Dressing wound treatment. Modern dressing is more effective for diabetic foot ulcer care because it accelerates new tissue growth, reduces pain, and lowers the risk of infection.